2021
DOI: 10.1186/s12885-021-08940-z
|View full text |Cite
|
Sign up to set email alerts
|

Survival impact of additional chemotherapy after adjuvant concurrent chemoradiation in patients with early cervical cancer who underwent radical hysterectomy

Abstract: Background To determine whether additional chemotherapy after concurrent chemoradiation (CCRT) improves survival outcomes in patients with early cervical cancer who undergo radical hysterectomy (RH). Methods We included high- or intermediate-risk patients from two institutions, with 2009 FIGO stage IB–IIA, who underwent primary RH and pelvic lymphadenectomy between January 2007 and June 2020, and had completed adjuvant CCRT. Survival outcomes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…However, because of the absence of specific clinical presentations at the initial stage of CC, the disease has always reached the advanced stage when patients are treated. In addition, the indications for surgical treatment are limited by tumor staging, coupled with serious side effects caused by radiotherapy and chemotherapy, causing serious psychological and physiological impacts on women [ 3 ]. Therefore, it is urgent to establish a more effective strategy for early diagnosis and targeted therapy of CC.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the absence of specific clinical presentations at the initial stage of CC, the disease has always reached the advanced stage when patients are treated. In addition, the indications for surgical treatment are limited by tumor staging, coupled with serious side effects caused by radiotherapy and chemotherapy, causing serious psychological and physiological impacts on women [ 3 ]. Therefore, it is urgent to establish a more effective strategy for early diagnosis and targeted therapy of CC.…”
Section: Introductionmentioning
confidence: 99%
“…However, the platinum and taxane combination has been preferred for its response and tolerable toxicities 24 25. In previous studies, the results of additional chemotherapy after concurrent chemoradiation were conflicting and might have been due to inconsistency in agents or regimens administered 9 10. In contrast, the STARS trial and the present study were consistent in the regimens for both concurrent chemoradiation and sequential chemoradiation 11.…”
Section: Discussionmentioning
confidence: 53%
“…Consolidation chemotherapy is another option that was evaluated in node-positive cervical cancer after radical hysterectomy; it showed improved survival in patients with more than three positive nodes or more than two positive nodes with lymphovascular space invasion and stromal invasion greater than 1/3 10. In another study, Kim et al reported that additional chemotherapy after post-operative concurrent chemoradiation did not improve survival in high- or intermediate-risk patients (disease-free survival, p=0.539; overall survival, p=0.121); however, a significantly higher number of patients with lymph node metastasis were in the study group (72.1%) compared with the control group (46.0%) 9. Although insufficient data suggest the benefit of consolidation chemotherapy, a phase III open-label randomized trial and other retrospective studies reported improved survival in locally advanced cervical cancer 18–21…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations